La bailoterapia en la coordinación rítmica en los jóvenes - Pisango Tapuy, Cinthia Karla (2025)
The present research work entitled “Dance Therapy in Rhythmic Coordination in Fourth Semester Students of the Pedagogy of Physical Activity and Sports Program at UNACH” aims to determine the impact of dance therapy on rhythmic coordination in fourth-semester students of the Pedagogy of Physical Activity and Sports program at UNACH. It was necessary to use the T40 Test as the data collection method, which is a test commonly used to assess rhythmic coordination and the ability to synchronize motor skills with auditory or visual stimuli. The research uses a quantitative approach to evaluate student rhythmic coordination improvements following a dance therapy program. The type of research is classified as quasi-experimental, as it manipulates a single variable. The study used a pretest and post-test design to collect data before and after the intervention. A non-probabilistic convenience sampling method included 22 students from the Pedagogy of Physical Activity and Sports program at the Universidad Nacional de Chimborazo.